Application of 3D Resistivity Method for Distribution of Seawater Intrusion in The Tanah Mas Residential North Semarang - Andya Satya Purnomo Putro; Supriyadi Supriyadi; Khumaedi Khumaedi (Natural B, Journal of Health and Environmental Sciences, 2016)
The seawater intrusion into the groundwater in Tanah Mas residential North Semarang was investigated by chlorides ion levels from production wells and 3D electrical resistivity profiling. Tanah Mas residential area is a densely populated area located in the northern coastal city of Semarang. At the area, the exploitation of groundwater through production wells is quite high, that potential to produce the phenomenon of seawater intrusion. Analysis of groundwater samples from production wells was carried out as an early indication of the seawater intrusion in the study area. The profiles acquired across the study area, using a multi-electrodes acquisition system in a Wenner array configuration by electrode spacing of 10 m were used for the profiling. The results of groundwater chemical testing, there are three groundwater samples that has high levels of chloride ions. Three groundwater samples have the high levels of chloride ions that are in wells F, J and M. Apparent resistivity data of the 2D profiles over the models were collated to 3D data sets for each array studied. From 3D electrical resistivity profiling, obtained the distribution of seawater intrusion that has reached the north, east and south of Tanah Mas residential.